Impact of pelvic biometric measurements, visceral and subcutaneous adipose tissue areas on trifecta outcome and surgical margin status after open radical retropubic prostatectomy. (April 2014) - Ongun, Sakir; Demir, Omer; Gezer, Naciye Sinem; Gurboga, Ozgur; Bozkurt, Ozan; Secil, Mustafa
Abstract: Objective. There is no sufficient evidence to demonstrate whether more challenging pelvic anatomy affects the functional and oncological outcomes of radical retropubic prostatectomy (RP). The aim of this study was to investigate the impact of pelvic biometric measurements, visceral and subcutaneous adipose tissue areas on trifecta outcome (cancer control, continence and potency) and surgical margin status after open RP. Materials and methods. A retrospective study was performed on 270 patients who were diagnosed with clinically localized prostate cancer between 2005 and 2011 and underwent computed tomography imaging before RP. Pelvic bony and soft-tissue measurements, and visceral and subcutaneous adipose tissue area calculations were performed. Patients were evaluated for trifecta outcome and surgical margin status on univariate and multivariate analyses. Subgroup analysis was performed for prostate volume, body mass index (BMI) and D'Amico risk classification. Results. Univariate analysis revealed that patients with trifecta were younger, and had lower prostate-specific antigen (PSA) levels, wider symphysis angle, and narrower prostate width and soft-tissue width ( p < 0.05). Patients with positive surgical margins were older, and had higher PSA levels, lower prostate volume and narrower prostate width ( p < 0.05). Visceral adipose tissue area was lower in patients with trifecta when BMI was below 25 kg/cm² ( p < 0.05). In multivariate analysis, PSA level and symphysis angle were statistically significant for trifecta while PSA level was the only statistically significant variable for positive surgical margins ( p < 0.05). Interfemoral index was significant in the low-risk group of D'Amico classification for trifecta outcome. Conclusion. Pelvic biometric measurements and adipose tissue area calculations may help in preoperative planning and the management of RP.